Antibodies response in symptomatic and asymptomatic SARS-CoV-2 infected persons in Thailand - Chanida Ruchisrisarod; Phanni Wanthong; Yutthana Joyjinda; Saowalak Bunprakob; Pasin Hemachudha; Anek Mungaomklang; Thirawat Supharatpariyakorn; Thiravat Hemachudha; Abhinbhen Saraya Wasontiwong (PLoS ONE, 2025)
Antibody assays of IgM, IgG and surrogate isotype independent virus neutralizing antibody (sVNT) targeting receptor binding domain of Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) were employed in 97 real-time Reverse Transcription Polymerase Chain Reaction (RT-PCR) confirmed Coronavirus Disease 2019 (COVID-19) patients with varying severity admitted to King Chulalongkorn Memorial Hospital. Concordance rate was 100% regardless of severity, onset of symptoms and magnitude of viral load. Per available samples, antibodies appeared on the same day of symptom onset in one patient; one day after in 18 patients and two days after in 19 patients. In two patients, antibodies appeared as early as 4 days after infection (exposure). IgM and IgG were evident in all patients’ first assay (within two days of admission). sVNT was also evident within two days of admission in all but 3 patients. IgM usually remained positive during the entire course of hospital stay, where the longest in this study was 32 days. Antibody assays were also applied to samples collected at a State Quarantine premise from 77 asymptomatic Thais returning from Sudan in October. Virus was detected by real-time RT-PCR in 15 cases (day 0 = 6, day 3 = 4, day 5 = 4 and day 9 = 1). Twenty-nine (including 11 RT-PCR positive cases) were antibody positive on day 0, while 4 PCR positive with antibody negative on day 0 became antibody positive on day 14. Evaluation on antibody response at days 7 or 10 is needed to help build a case to shorten length of quarantine among negative cases.